PENGEMBANGAN BAHAN AJAR MATERI SEGITIGA MELALUI PMRI DI SEKOLAH MENENGAH PERTAMA - Selvi Riwayati; Kiky Ridzky (Jurnal Math-UMB.EDU, 2020)
This study aims to know whether teaching materials developed were valid and practical at the triangle of material through PMRI in junior high school. The research began by interviewing teachers in SMPN 2 Bengkulu city was obtained information that in mathematics on triangular material still has difficulty at understanding the concept. The teaching material developed in this study was in the student books, teacher books and lesson plan (RPP). Development of this resource referred to the mode of development of 4-D (four-D) that was Define, Design, Develop, Disseminate. However, this study was only done until the stage of development (development) only. At the defining stage has been done as much as five steps of the activity. At the design stage, researchers prepared a prototype by designing instructional materials in the form of books developed through PMRI.KeywordsÂ  :Teaching materials, Triangle, PMRI